A transient, three-dimensional numerical study of chemical vapor deposition in batch reactors - Wangard, William, III, author; Dandy, D. S., advisor; Burns, Patrick J., advisor (Colorado State University. Libraries, 2001)
A time-accurate model of multicomponent reacting flow with homogeneous and heterogeneous chemical reactions was developed to simulate the transport phenomena, gas-phase chemistry, and deposition profiles in constant-volume chemical vapor deposition reactors with arbitrarily complex geometry in two or three dimensions. A fully rigorous multicomponent gas transport model including thermal diffusion was used. A transformation was applied to the matrix of ordinary diffusion coefficients to form a matrix of effective ordinary diffusion coefficients. This transformation permitted a decoupling of the species continuity equations from one another. A first-order, time-accurate splitting procedure was used to integrate the species and energy equations, which were stiff due to terms arising from the homogeneous and heterogeneous chemical reactions. The stiff equations were solved with the CVODE library. A variable-density projection method was used to solve the variable-property momentum equations. The partial differential equations describing the model were discretized using a conservative finite difference method implemented on overset grids. The overset method was used to obtain solutions on arbitrarily complex geometrical domains. A computer code was developed using the OVERTURE object-oriented class library. The CHEMKIN library was used to compute thermodynamic properties of multicomponent mixtures of ideal gases and homogeneous reaction rates. The CHEMKIN TRANSPORT library was used to compute multicomponent transport properties. The SURFACE CHEMKIN library was used to compute the heterogeneous reaction rates. Numerical simulations included natural convection in two-dimensional horizontal and tilted reactors, chemical vapor deposition in a three-dimensional reactor with a heterogeneous chemistry, chemical vapor deposition in a two-dimensional reactor with moderately complex homogeneous and heterogeneous chemistry, and a CPU timing study with a system with a complicated homogeneous and heterogeneous reaction model. Results indicated that the solver obtained accurate solutions in CVD batch systems having complicated homogeneous and heterogeneous reaction models for both small and moderate Rayleigh number flows.
Keywords: mechanical engineering; chemical engineering